The in situ gas‐phase formation of a C‐glycoside ion obtained during electrospray ionization tandem mass spectrometry. A unique intramolecular mechanism involving an ion‐molecule reaction. (25th August 2015) - Banoub, Joseph H.; Demian, Wael L. L.; Piazzetta, Paolo; Sarkis, George; Kanawati, Basem; Lafont, Dominique; Laurent, Nicolas; Vaillant, Celine; Randell, Edward; Giorgi, Gianluca; Fridgen, Travis D.
<x xml:space="preserve">Abstract</x> Rationale This study examines the electrospray ionization mass spectrometry (ESI‐MS), in‐source collision‐induced dissociation (CID) fragmentation and low‐energy collision‐induced dissociation tandem mass spectrometry (CID‐MS/MS) of a synthetic pair of β‐ and α‐anomers of the amphiphilic cholesteryl polyethoxy neoglycolipids containing the 2‐azido‐2‐deoxy‐D‐galactosyl‐D‐GalN3 moiety. We describe the novel and unique in situ gas‐phase formation of a C‐glycoside ion formed during all these gas‐phase processes and propose a reasonable mechanism for its formation. Methods The synthetic amphiphilic glycolipids were composed of the 2‐deoxy‐2‐azido‐D‐galactosyl moiety (GalN3, the hydrophilic part) covalently attached to a polyethoxy spacer which is covalently linked to the cholesteryl moiety (hydrophobic part). The 2‐azido‐2‐deoxy‐α‐ and β‐D‐galactosyl‐containing glycolipids were studied by in‐time and in‐space ESI‐MS and CID‐MS/MS in positive ion mode, with quadrupole ion trap (QIT), quadrupole‐quadrupole‐time‐of‐flight (QqTOF), and Fourier transform ion cyclotron resonance (FTICR) instruments. Results Conventional single‐stage ESI‐MS analysis showed the formation of the protonated molecule. During the single‐stage ESI‐MS analysis and the CID‐MS/MS of the [M+H]+ and [M+NH4]+ adducts obtained from both glycolipid anomers, the presence of a series of specific product ions with different intensities was observed, consistent with the [C‐glycoside+H–N2]+, [cholestadiene+H]+, 2‐deoxy‐2‐D‐azido‐galactosyl [GalN3]+, [GalNH]+ and [sugar−Spacer+H]+ ions. Conclusions The gas‐phase formation of the [C‐glycoside+H–N2]+ ion isolated from the glycolipid anomers was observed during both the ESI‐MS of the glycolipids and the CID‐MS/MS analyses of the [M+H]+ ions and it was found to occur by an intramolecular rearrangement involving an ion‐molecule complex. CID‐QqTOF‐MS/MS and CID‐FTICR‐MS2 analysis allowed the differentiation of the two glycolipid anomers and showed noticeable variation in the intensities of the product ions. Copyright © 2015 John Wiley & Sons, Ltd.